P479 Analysis of haematological changes in tofacitinib-treated patients with ulcerative colitis across Phase 3 induction and maintenance studies. (25th January 2019) - Lichtenstein, G R; Moore, G T; Soonasra, A; Nduaka, C I; Kwok, K; Wang, L; Lawendy, N; Chan, G; Su, C; Loftus Jr., E V
Abstract: Background: Tofacitinib is an oral, small-molecule JAK inhibitor approved in several countries for the treatment of ulcerative colitis. Changes in haematological parameters in participants of OCTAVE Induction 1 and 2 (NCT01465763 and NCT01458951) and OCTAVE Sustain (NCT01458574) 1 were evaluated. Methods: In OCTAVE Induction 1 and 2, patients received either placebo (PBO) or tofacitinib 10 mg twice daily (BID) for 8 weeks; clinical responders were re-randomised into OCTAVE Sustain for 52 weeks (received PBO, tofacitinib 5 or 10 mg BID). Mean absolute lymphocyte count (ALC), absolute neutrophil count (ANC), platelet count (PC) and haemoglobin (Hgb) level changes were analysed. Haematological adverse events (AEs) were evaluated. Results: Following 8 weeks of treatment (PBO or tofacitinib 10 mg BID) in OCTAVE Induction 1 and 2, Hgb levels, ALC and ANC were stable, while PC declined from baseline (Table). Up to Week 52 of OCTAVE Sustain, Hgb levels increased and ALC, ANC and PC declined in all groups (table). During OCTAVE Induction 1 and 2, AEs of anaemia were reported in 22 (2.4%) tofacitinib-treated patients compared with 9 (3.8%) placebo-treated patients. During OCTAVE Sustain, the incidence rates (IRs; unique patients with events per 100 patient-years) of anaemia were 2.91, 5.51, and 2.55 for PBO, tofacitinib 5 and 10 mg BID, respectively. No AEs of neutropenia were reported during OCTAVE Induction 1and2. In OCTAVE Sustain, IRs were 0.00, 0.67, and 0.64 for placebo, tofacitinib 5 and 10 mg BID, respectively. During OCTAVE Induction 1 and 2, 2 (0.2%) tofacitinib-treated patients had AEs of lymphopenia, and no AEs of lymphopenia occurred during OCTAVE Sustain. Discontinuations due to laboratory abnormalities were low. Two (0.2%) tofacitinib-treated patients discontinued in OCTAVE Induction 1 and 2 due to ALC decline (2 sequential readings <0.5 × 10 9 /l) and 5 (0.6%) tofacitinib-treated patients discontinued due to Hgb decline (2 sequential values < 0.8 g/dl or >30% decrease from baseline), compared with Hgb decline in 1 (0.4%) PBO-treated patient. In OCTAVE Sustain, 1 (0.3%) pt discontinued due to Hgb decline. Conclusions: In OCTAVE Sustain, treatment with both tofacitinib doses resulted in decreased ALC, ANC and PC, and increases in Hgb levels. There was no dose dependency in anaemia or neutropenia IRs. Similar trends were observed in rheumatoid arthritis (RA) patients treated with tofacitinib. 2 Increases in Hgb were also found in IBD and RA patients treated with TNFi. 3–5 References 1. Sandborn WJ, Su C, Sands BE, et al. Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med 2017;376:1723–36 2. Schulze-Koops H, Strand V, Nduaka C H et al. Analysis of haematological changes in tofacitinib-treated patients with rheumatoid arthritis across phase 3 and long-term extension studies. Rheumatology 2017;56:46–57. [3] Koutroubakis IE, Ramos-Rivers C, Regueiro M, et al. The influence of anti-TNF agents on hemoglobin levels of patients with inflammatory bowel disease. Inflamm Bowel Dis 2015;21:1587–93 4. Rubin DT, Rubin DT, Mulani P, Chao J, et al . Effect of adalimumab on clinical laboratory parameters in patients with Crohn's disease: results from the CHARM trial. Inflamm Bowel Dis 2012;18:818–25. 5. Doyle MK, Rahman MU, Han C, et al. Treatment with infliximab plus methotrexate improves anemia in patients with rheumatoid arthritis independent of improvement in other clinical outcome measures—a pooled analysis from three large, multicenter, double-blind, randomized clinical trials. Semin Arthritis Rheum 2009;39:123–32.